Optimizing Board Effectiveness with Gender Diversity : Are Quotas the Answer? - Durbin, Annemarie (World Bank, Washington, DC, 2012)
Women are underrepresented on corporate boards but are quotas the answer? Not according to the author. Annemarie Durbin cites evidence that using quotas to increase female representation can lead to tokenism, diminish the overall value of diversity on boards, affect board dynamics, and potentially lead to diluted commitments from existing female board directors. She recommends that, instead of quotas, companies should take a holistic approach toward improving board nominating criteria and processes, developing female middle and senior management talent, and ensuring positive dynamics among diverse board members.